Beards and Bloomers: Flight Attendants, Grievances and Embodied Labour in the Canadian Airline Industry, 1960s–1980s - Sangster, Joan; Smith, Julia Maureen (Gender, Work & Organization, 2016)
This paper examines union grievances dealing with the body, appearance and demeanour fought by the Canadian Air Line Flight Attendants Association, on behalf of its female and male members over a 30-year period. Taking a historical, materialist-feminist approach, we examine how workers used the grievance system to resist regulations they believed contradicted their right to dignified labour. We ask how and why bodily regulation differed for men and women, and how this changed over time, as the union merged its male and female job occupations. Using arbitrated grievances, union records and discussion of these issues in the mass media, we show how both feminism and service union activism encouraged flight attendant resistance to airlines’ efforts to regulate the appropriate body and attire for male and female workers. The use of labour law offered workers some respite from regulation, but did not facilitate fundamental questions about the power of management to ‘dress’ its workers.
Keywords: arbitration; flight attendant unions; gendered work; grievances; labour law